Study on the Strength Development of Cemented Backfill Body from Lead-Zinc Mine Tailings with Sulphide. (16th April 2018) - Zheng, Juanrong; Guo, Lijie; Sun, Xiaoxiao; Li, Wenchen; Jia, Qi
Abstract : The unconfined compressive strength (UCS) development of cemented backfill materials for lead-zinc mine tailings with sulphide was studied. The results showed that the UCS of the cemented backfill body with ordinary Portland cement (OPC) as binder decreased in the later curing days, regardless of particle size. Under the same conditions, the higher the OPC content, the higher the UCS of the cemented backfill body, and the UCS of the cemented backfill body began to decrease at the longer curing days. Under the same conditions, the finer the tailings, the lower the UCS of the cemented backfill body at each age, and the UCS of the cemented backfill body began to decrease at the earlier curing age. X-ray diffraction analysis (XRD) showed that the reduction of the UCS of the cemented backfill body was related to the formation of an expansive substance (expansive gypsum) in the cemented backfill body, which led to the cracking of the test sample. In the cemented backfill materials of coarse tailings of lead-zinc mine, the composite binder formed by OPC and calcined kaolin (CK) containing metakaolin was used; the amount of calcium hydroxide, the hydration product of cement, was reduced or eliminated due to the pozzolanic reaction of metakaolin; and the amount of expansive gypsum was reduced or eliminated, so the UCS of the cemented backfill body increased within 360 days of curing.